The acid mine drainage (AMD) impact of tailings and non-tailings on the ecosystem changes in the ModADA sedimentation area, Timika - Sartji Taberima; Edy Junaedi; Roberth Sarwom; Linda Ernawati Lindongi; Budi Mulyanto (Journal of Degraded and Mining Lands Management, 2020)
Tailings are the parent material residues resulted from a separation process of valuable minerals containing copper, gold and silver. This separation process is carried out mechanically by destroying copper, gold and silver rocks on the Grasberg plateau. However, in the production process of tailing materials from Wanagon and Aghawagon rivers, there was also non-tailing material mixed with tailing materials. This condition cannot be avoided due to high and intensive rainfall so that non-tailing material from an ex-mine excavation in the form of overburden can flow naturally through the river flow system from the highlands to the lowlands of ModADA. Acid Mine Drainage (AMD) is one of the important impacts of mining activities that must be managed because it has an impact on the aquatic environment or groundwater, and once it has been formed it will be difficult to stop unless one of the components runs out. The study was carried out from 2005 to 2014 at several representative locations in ModADA included inactive tailings at MP 27 and MP 21, as well as active tailings at WA 225, WA 185, and WA 160. The average heavy metal content in WA 225, WA 185, WA 160 included in the criteria of class C, namely As (> 33 mg/kg), Cu (> 150 mg/kg), Pb (> 130 mg/kg), and Zn (> 460 mg/kg). Another heavy metal categorized as class B was Cd (1-5 mg/kg), while class A consisted of Cr (<43 mg/kg), Hg (<0.2 mg/kg), and Ni (<23 mg/kg). At WA 185, The ANC/MPA ratio at WA 185 < 1.5 was 0.97 (0-20 cm) and increased slightly to 1.59 (20-40 cm). The ANC/MPA ratio < 1.5 shows a higher acid-forming ability (MPA) than the ability to neutralize acid (ANC). The average heavy metal content in MP 27 is lower in concentration, except Cu which included in class C (> 150 mg/kg) which is similar to the host rock mined and involved in the tailings flow from MP 74. The Cu concentration at MP 21 decreased drastically, except for As which included in class C (> 33 mg/kg). The ANC/MPA ratio at MP 21 was 1.92 (0-20 cm) and slightly increased to 2.22 (20-40 cm), while MP 21 has the ANC/MPA ratio at 12.61 (0- 20 cm), and decreased to 4.34 (20-40 cm).